Hermeneutics in the Genre of Mukhtaṣar: Civil and Commercial Law in Islamic Law by Husain Kassim (American Journal of Islam and Society, 2020)
Historically, mukhtaṣar (abridged) works have played a significant role in the Islamic tradition as easy-to-memorize legal manuals. They concisely condense the corpus juris in all its enormous detail and outline the basic structure of the law around legal maxims and principles. In fact, as early as the fourth/tenth century, every school had already selected a mukhtaṣar, not only as a standard pedagogical manual but also as an authoritative survey of its substantive law. Despite its importance as a legal genre, however, few scholars have singled out the mukhtaṣar as a single unit of analysis nor studied its role in shaping and systemizing Islamic law.To read the full book review, download the PDF file on the right.